A Metro Map Can Tell A Story, As Well As Provide Good Directions - Shahaf, Dafna; Guestrin, Carlos; Horvitz, Eric; Leskovec, Jure (Communications of the ACM, 2015)
A metro map can tell a story, as well as provide good directions.